2022
DOI: 10.1177/10711007221119157
|View full text |Cite
|
Sign up to set email alerts
|

Two Orthogonal Nitinol Staples and Combined Nitinol Staple-Screw Constructs for a First Metatarsophalangeal Joint Arthrodesis: A Biomechanical Cadaver Study

Abstract: Background: End-stage hallux metatarsophalangeal (MTP) joint arthritis is commonly treated with arthrodesis using stainless steel or titanium implants. These implants provide static compression that is maximal at the time of implant insertion. Alternatively, nitinol staples are capable of dynamic compression. They have most frequently been used for midfoot arthrodesis procedures. However, their biomechanical performance during hallux MTP arthrodesis has not been described. Methods: 8 matched pairs of cadaveric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Across the 20 included articles, there were a total of 143 pairs of human cadaveric toes, 16 pairs of porcine cadaveric toes, and 92 synthetic bone models for a total of 446 cases of first MTP arthrodesis [1,9,11,13,19,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Arthrodesis was achieved using a variety of modalities including dorsal plates, interfragmentary lag screws, K-wires, wire sutures, and staples.…”
Section: Study Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Across the 20 included articles, there were a total of 143 pairs of human cadaveric toes, 16 pairs of porcine cadaveric toes, and 92 synthetic bone models for a total of 446 cases of first MTP arthrodesis [1,9,11,13,19,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Arthrodesis was achieved using a variety of modalities including dorsal plates, interfragmentary lag screws, K-wires, wire sutures, and staples.…”
Section: Study Demographicsmentioning
confidence: 99%
“…Neufeld et al also compared shape-memory staples to cross-cannulated screws as well as a dorsal plate, finding that the staples did indeed fail at significantly lower loads than the crossed-cannulated screws (p < 0.029) and the dorsal plate (p < 0.002) [36]. Schafer et al similarly compared orthogonal nitinol staples to a dorsal staple with a crossed screw [30]. All eight specimens implanted with orthogonal staples failed at an average of 37 ± 81 cycles of a 90 N, 250,000 cycle protocol designed to simulate 6 weeks of postoperative weightbearing due to excessive gap formation > 7 mm.…”
Section: Staple Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…The MPA1 procedure can vary depending on the type of joint surface resection and fixation method. For instance, these surgeries may rely on different types of joint surface resections, such as flat, concave, or convex, and various fixation methods, including screws, plates, or staples [10][11][12]. These different techniques can affect the effectiveness and outcomes of the surgical procedure.…”
mentioning
confidence: 99%
“…Notwithstanding the positive clinical results, and the ever-increasing number of commercially available nitinol staple products, there are potential inherent limitations to nitinol staples as a sole tool for midfoot and forefoot fusions and trauma. Schafer et al 8 reported a biomechanical comparison of a 90-degree orthogonal nitinol staple construct vs a compression screw and staple construct for metatarsophalangeal fusion. They found that 15 of 16 specimens failed during cyclic loading, with significantly earlier failure in the orthogonal staple group.…”
mentioning
confidence: 99%